The Impact of Multimedia in Teaching and Learning - Agaj, Fatmir (European Journal of Multidisciplinary Studies, 2016)
The innovations that happen in education seek for great leaders and with an outstanding professional background. The innovation managers are very open-minded to the changes that occur in schools, but unfortunately there are many of them who are closed to such changes in schools, the reason to resist is the lack of knowledge towards these educational innovations and of the changes that could be made in the schools and in the classrooms. Avoiding such problems could be made through active participation of the teachers in trainings, because the development of the technology and the improvement of the educational technology influences many changes in teaching methods and forms. Based on previous research it was seen that the role of multimedia in the classroom influences a great interest in participating actively in learning. This research was chosen intentionally with the reason of playing a positive role in raising the awareness of the community, with the argumentation of the hypothesis that multimedia in the learning process has a great role in purifying students with new information. Education, as a rule, slowly accepts any implementation of innovations in comparison with business, producing, transportation etcetera. In addition to it, implementing multimedia systems, distance learning, virtual schools etcetera would definitely increase the activity of the students in advancing their skills in comparison with their former background knowledge.